Rice Production in the Philippines and the Inverted U (Environmental Kuznets Curve) Hypothesis - Del Prado, Grace Edmar Elizar (JPAIR Multidisciplinary Research, 2010)
Proponents of the EKC hypothesis say that economic growth brings both improving and worsening environmental performance at different phases of the development process. At low-income level, the environmental impact per dollar GDP increases with increasing GDP per capita, while at high income it declines. Nobel Prize winner Kenneth Arrow and a few critics more conceded the validity of the hypothesis explaining that this has to be valid only for pollutants involving local short-term costs. Redefining such framework, variables on population, land area used for rice production, temperature, average rainfall and amount of particulates in the atmosphere were regressed to find each individual and collective impact to the country’s rice production trend from 1991-2004. Results supported the Environmental Kuznets Curve hypothesis showing that rice production increased over time as rainfall and temperature accelerate but reversed its direction as these factors escalate excessively.